Perception of Japanese Students in Using Online Video as A Learning Media - Rahayu Siwi Winarni; Linna Meilia Rasiban (Indonesian Journal of Educational Research and Technology, 2021)
The purpose of this research is to examine students' perceptions towards the use of YouTube as a teaching medium to increase students’ interest and motivation in learning Japanese. The method used is descriptive qualitative with survey techniques and literature research. The descriptive analysis is used to describe the percentage of each variable, namely the use of YouTube and Japanese students' interest and learning motivation. The results of this study indicate that YouTube offers a significant effect on students in the use of online video as a learning medium and the research findings show that the participants positively view the use of YouTube in their lessons. The result also revealed a significant increase in increasing student interest and motivation in learning Japanese. The results of this study can be an illustration to encourage students, especially in learning Japanese, to make the most of the online media or video channels on YouTube related to Japanese language learning. This research also can be an online learning system in technological development.